Cardiovascular Impairment in COVID-19: Learning From Current Options for Cardiovascular Anti-Inflammatory Therapy - Wang, Lun; Zhang, Yang; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2020)
In December 2019, Coronavirus Disease 2019 (COVID-19) caused by SARS-CoV-2, occurred in China and has currently led to a global pandemic. In addition to respiratory involvement, COVID-19 was also associated with significant multiple organ dysfunction syndrome (MODS). Cardiovascular impairment has been observed and is now drawing growing attention. Cardiovascular protective strategies are urgent and of great significance to the overall prognosis of COVID-19 patients. Direct viral infection, cytokine storm, and aggravation of existing cardiovascular diseases were recognized as possible mechanisms of cardiovascular impairment in COVID-19. Hyperactivated inflammation plays an important role in all three mechanisms and is considered to be fundamental in the development of cardiovascular impairment and MODS in COVID-19. Therefore, in addition to conventional cardiovascular treatment, anti-inflammatory therapy is a reasonable strategy for severe cases to further enhance cardiovascular protection and potentially mitigate MODS. We reviewed the inflammatory features and current promising treatments of COVID-19 as well as cardiovascular anti-inflammatory therapies that have been verified in previous clinical trials with positive outcomes. We believe that targeting the central pathway (IL-1β, TNF-α, IL-6), balancing the Th1 and Th2 response, and administering long-term anti-inflammatory therapy might be promising prospects to reduce cardiovascular impairment and even MODS during the acute and recovery phases of COVID-19. The cardiovascular anti-inflammatory therapies might be of great application value to the management of COVID-19 patients and we further propose an algorithm for the selection of anti-inflammatory therapy for COVID-19 patients with or at high risk of cardiovascular impairment. We recommend to take the experiences in cardiovascular anti-inflammatory therapy as references in the management of COVID-19 and conduct related clinical trials, while the clinical translation of novel treatments from preclinical studies or in vitro drug screening should proceed with caution due to unguaranteed efficacy and safety profiles.